Adaptação cultural e evidência de validade da Quality of Life Scale for Informal Carers for Older Adults (QoL-IC) e da Care Experience Scale (CES) para o contexto brasileiro - Frisanco, Fernanda Menegatti (Universidade Federal de São Carlos, 2026)
Population aging has increased the demand for informal caregivers, whose quality of life (QoL) and care experience still lack specific and validated instruments for the Brazilian context. This study aimed to translate, culturally adapt, and examine validity evidence of the Quality of Life Scale for Informal Carers for Older Adults (QoL-IC) and the Care Experience Scale (CES) for use in Brazil. This was a methodological study conducted in two stages: (1) translation and cultural adaptation according to international guidelines, and (2) evaluation of psychometric properties, including exploratory and confirmatory factor analyses, internal consistency, test–retest reliability, and construct validity using external measures. The Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) and the Patient Health Questionnaire–2 (PHQ-2) were used for construct validation. Convergent validity was assessed through correlations between CES and QoL-IC scores and SF-36 domains, while discriminant validity was examined using cross-loadings and known-groups comparisons between caregivers with and without burden, assessed by the Brief Zarit Burden Interview (ZBI-12), and with and without depressive symptoms, assessed by the PHQ-2. Thirty five caregivers participated in the pretest, and 240 informal caregivers were included in the psychometric evaluation, all recruited from the Programa Melhor em Casa in Mogi Guaçu, São Paulo, Brazil. Cultural adaptation followed ethical principles and recommended procedures, with conceptual and cultural equivalence confirmed by six expert judges. For the CES, exploratory factor analysis identified a two-factor structure; after exclusion of one item with low factor loading, the two factors explained 58.3% of the total variance. Test–retest reliability was excellent (ICC = 0.984). The CES showed significant negative correlations with SF-36 domains, including physical functioning (r = –0.141; p = 0.028), general health (r = –0.159; p = 0.013), vitality (r = –0.145; p = 0.024), and the physical (r = –0.250; p = 0.020) and mental (r = –0.293; p = 0.027) component summaries, as well as a moderate positive correlation with PHQ-2 scores (r = 0.311; p = 0.032). Caregivers with burden and depressive symptoms presented higher CES scores (p < 0.05). CES scores were significantly associated with all QoL-IC domains, particularly exhaustion, support for caring, financial issues, and personal growth (p < 0.001). For the QoL-IC, confirmatory factor analysis retained the six-domain structure after excluding items 8 and 24, with factor loadings ≥ 0.40. Internal consistency ranged from 0.47 to 0.92. Correlations with SF-36 domains were weak to moderate (r = 0.262–0.307; p = 0.002–0.012), and negative associations were observed between exhaustion and depressive symptoms (r = –0.417; p < 0.001). Caregivers without burden and depressive symptoms showed higher QoL scores in several domains and in the total score (p < 0.05). The CES and QoL-IC demonstrated preliminary evidence of validity and reliability for use in Brazil, supporting their applicability in research, clinical practice, and public policies targeting informal caregivers of older adults.
Cultural adaptation and validity evidence of the Quality of Life Scale for Informal Carers for Older Adults (QoL-IC) and the Care Experience Scale (CES) for the Brazilian context.
Keywords: Cuidadores informais; Envelhecimento; Qualidade de vida; Adaptação cultural; Psicometria; Validação; Informal Caregivers; Aging; Quality of Life; Cultural Adaptation; Psychometrics; Validation; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE; 3. Saúde e Bem-Estar